Problem-Solving-Oriented Training Teaching Method to Improve Mathematical Logical Reasoning Ability on Middle School Students - Moqian Moqian; Jerito Pereira (IKIP Siliwangi, 2022)
With the deepening of the reform and development of the new curriculum education in the 21st century, the mathematics core accomplishment has been paid more and more attention by middle school teachers, among which, the logical reasoning ability is one of the important contents of the mathematics core accomplishment in middle school. The research purpose of this paper is to solve the problem of middle school students mathematical logical reasoning ability is not strong, starting from the mathematical problem itself, to explore how to cultivate students' logical reasoning thinking ability and teaching methods. This paper adopts the literature analysis method to summarize and analyze the relevant literature, uses the case analysis method to deeply analyze the relevant classic examples, and uses the statistical analysis method to analyze the students' logical reasoning literacy. Through the analysis of cases and students, this study believes that having the ability of mathematical logic reasoning can help students to solve mathematical problems, and similarly, it also promotes the development of students' mathematical logic reasoning ability in the process of solving problems. When cultivating students logical reasoning ability in problem-solving problems, we can start from the following aspects, 1. Pay attention to the study of basic knowledge, 2. Cultivate students' observation ability, 3. Analysis and prove with the help of innovative problems.